New soliton solutions for Sasa-Satsuma equation - Demiray, Seyma Tuluce; Pandir, Yusuf; Bulut, Hasan (Taylor & Francis Ltd, 2015)
In this work, we survey exact solutions of Sasa-Satsuma equation (SSE). We utilize extended trial equation method (ETEM) and generalized Kudryashov method to acquire exact solutions of SSE. First of all, we gain some exact solutions such as soliton solutions, rational, Jacobi elliptic, and hyperbolic function solutions of SSE by means of ETEM. Furthermore, we procure dark soliton solution of this equation by the help of generalized Kudryashov method. Lastly, for certain parameter values, we draw two- and three-dimensional graphics of imaginary and real values of some exact solutions that we achieved using these methods.
Keywords: Conservation-Laws; Rogue Waves